Social Dimension of the Russian Armed Forces Reform - Olszanecka, Natalia (Przegląd Wschodnioeuropejski, 2019)
At the beginning of the 1990s the political and military global reality was radically transformed. It affected all spheres of socio-political life and was visible also in the armed forces. At the beginning of the second decade of the 21st century, the Russian armed forces were still one of the most troubling military mechanisms in the world. In 2007 the Minister of Defense Anatoly Serdyukov decided to implement a broad military reform, which included (besides organizational issues and modernization of military equipment) also social issues. The aim of this article is to analyze the second stage of the armed forces reform in Russia (2010–2015) that entailed improvement of material status and livelihood of soldiers. The main research method used in this article was content analysis. A particularly important source was the study conducted by Irina Surkowa and articles published in Russian newspapers. The analysis showed that the reforms initiated by Serdyukov considerably improved the living conditions of the soldiers.